Polycyclic aromatic hydrocarbons in the occupational environment: with special reference to benzo[a]pyrene measurements in Swedish industry. - Lindstedt, Gösta; Sollenberg, Jan (Scandinavian Journal of Work, Environment & Health, 1982)
A review is given of measurements of polycyclic aromatic hydrocarbons (PAH) in the work environment in general with emphasis upon Swedish measurements of benzo[a]pyrene not previously published in international literature. Finally, epidemiologic investigations on PAH exposed workers, as well as threshold limit values for PAH, are discussed.
Keywords: benzo[a]pyrene measurement; coal tar pitch volatile exposure; epidemiology; exposure; industry; occupational environment; PAH; polycyclic aromatic hydrocarbon; Sweden; threshold limit value